Using Factorization to Estimate the Charmed Meson Decays - Huong, Nguyen Thu; Bang, Ha Huy (VNU Journal of Science: Mathematics - Physics; Vol 32 No 3DO - 10.25073/2588-1124/vnumap.4053, 2016)
Abstract: Study of the charmed meson decays is mentioned in the articles [1, 2]. These researches help to improve the results of light mesons decays. In this paper, applying the factorization method, we try to estimate the branching ratios of charmed meson decays, namely . This can be an effective method for computing the decay rates of new channels. Keywords: Factorization, charmed meson decays, operator product expansion.